Model Sistem Informasi Pengajuan Kredit Berbasis Web pada Bank Perkreditan Rakyat - Nurhadi Nurhadi; Fevi Istiani (STMIK Banjarbaru, 2022)
The length of the credit application process at Rural Banks is one of the obstacles that must be faced by prospective customers. The procedure for filling out paper forms is less effective if the prospective customer is outside the region, because information about the prospective customer is the main key in applying for credit. While the facilities for applying for credit are often limited, credit analysts must provide more detailed and faster information about prospective customers so that the credit disbursement process can be carried out. The purpose of writing this article is to present an information system model to speed up and make it easier for customers to apply for credit, this credit application information system is web-based so that users can apply for credit from anywhere and anytime, and use the prototype method to ensure that the information system is in accordance with user needs. The results of application testing with Black Box Testing show that the functional features of the application system have run according to system requirements and the features are made in accordance with the user's requirements requested during the Communication stage contained in the prototype method.Keywords: credit application; information Systems; method prototype; PHP; MySqlLamanya proses pengajuan kredit pada Bank Perkreditan Rakyat adalah salah satu kendala yang harus dihadapi oleh calon nasabah. Prosedur mengisi formulir berupa kertas, kurang efektif apabila calon nasabah berada luar daerah, karena informasi mengenai calon nasabah menjadi kunci utama dalam pengajuan kredit. Sedangkan sarana di dalam pengajuan kredit pun kerapkali terbatas, para analis kredit harus menyajikan informasi mengenai calon nasabah yang lebih detail dan cepat agar proses pencairan kredit bias dilakukan. Tujuan dari penulisan artikel ini adalah menyajikan model sistem informasi untuk mempercepat dan memudahkan nasabah dalam mengajuan kredit, sistem informasi pengajuan kredit ini berbasis web sehingga pengguna dapat melakukan pengajuan kredit dari mana saja dan kapan saja, serta menggunakan metode prototype untuk memastikan bahwa sistem informasi sesuai dengan kebutuhan pengguna. Hasil pengujian aplikasi dengan Black Box Testing menunjukkan fitur-fitur fungsional pada sistem aplikasi telah berjalan sesuai kebutuhan sistem dan fitur-fitur yang dibuat sesuai dengan kebutuhan pengguna yang diminta pada saat tahapan Communication yang terdapat pada metode prototype.